A new species of Naultinus from the Te Paki area, northern New Zealand - Hitchmough, Rodney A.; Nielsen, Stuart V.; Lysaght, Judith A.; Bauer, Aaron M. (Zootaxa, 2021)
We describe a new species of the New Zealand diplodactylid gecko genus Naultinus. Molecular phylogenetics and distinctive morphological features support taxonomic separation of the populations on the northern half of Aupori Peninsula in the far north of the North Island as a new species, Naultinus flavirictus sp. nov. The specific epithet refers to the diagnostic yellow colour at the corners of the mouth. We discuss the conservation status of and threats to this novel taxon and to Te Paki, Northland—the unique area of New Zealand where it is found. We further discuss the distribution and possible function of bright mouth colour within Naultinus.